ALZHEIMER'S DISEASE THERAPEUTIC APPROACHES - A, Sandhya; Kannayiram, Gomathi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
A protein is a large biomolecule which consists of one or more chains of amino acid residues. Proteins exhibit a biological phenomenon in which, they are misfolded as aggregates (i.e., accumulate and clump together) either intra- or extracellularly. This process plays a central role in the pathogenesis of Alzheimer's disease (AD) and diabetes mellitus (DM) - 2 and common for many degenerative diseases. In this case, the histopathological consequences of protein misfolding such as sensile plaques and neurofibrillary tangles in AD and lewy bodies in Parkinson's disease occur. 8–10% of adult population shares risk factors with AD. Amyloid fibrils which build up in tissue as an abnormal protein form Amyloidosis. Conformational change in three-dimensional structure forms amyloid fibrils. Type 2 DM is characterized by the deposition of islet amyloid polypeptide within beta cells of the pancreas which leads to chronic cerebral hypoperfusion that result in degeneration of neuroglial cells.